Simultaneous determination of organic analytes by reduced graphene oxide-azo dyes/gold nanoparticles modified glassy carbon electrode - Alshik Edris, Nusiba Mohammed Modawe (2019)
The detection of biological molecules and monitoring of environmental contaminants is a demanding aspect in the field of analysis. Electrochemical sensors are one of the tools that attracted great attention in this field due to their applicability. In the present research work, glassy carbon electrode (GCE) was modified by electrochemically reduced graphene oxide (ERGO) with two different azo dyes i.e. poly(eriochrome black T) (pEBT) and poly(Procion Red 5-MX) poly (PR) and gold nanoparticles (AuNPs) to obtain AuNPs/ERGO-pEBT/GCE and AuNPs/ERGO-poly(PR)/GCE electrochemical sensors. The modified sensors were characterised by field scanning electron microscopy (FESEM), Fourier transform infrared spectroscopy (FTIR), electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV). The resultant modified sensors revealed elevated electrocatalytic properties in comparison to other modified GCEs. The prepared nanocomposites were used to simultaneously determine ascorbic acid (AA), dopamine (DA), and uric acid (UA) as well as hydroquinone (HQ), catechol (CC), and resorcinol (RC) in phosphate buffer solution (PBS). Due to the synergistic effect, the modified electrodes had excellent electrochemical catalytic activity towards the oxidation of two sets of analytes which allowed their simultaneous determination. The AuNPs/ERGO-pEBT/GCE showed good potential peak separations of 166 and 126 mV for DA-AA and UA-DA respectively when it was immersed in a mixture solution of AA, DA, and UA. Simultaneous detection of HQ, CC, and RC was performed with potentials separation of 111 and 383 mV for HQ-CC and CC-RC, respectively, thus acknowledged the simultaneous detection of these isomers.In the same manner, AuNPs/ERGO-poly(PR)/GCE was used to simultaneously determine AA, DA, and UA where, the potential separations between DA-AA and UA-DA were found to be 210 and 140 mV, respectively. The modified electrode (AuNPs/ERGO-poly(PR)/GCE) has also been utilised in the simultaneous detection of HQ, CC, and RC. DPV was carried out and the peak potential separation between HQ-CC was 130 mV and CC-RC was 400 mV. AuNPs/ERGO-pEBT/GCE revealed limit of detections (LODs) of 530, 9, and 46 nM, with sensitivities of 0.003, 0.164, and 0.034 μA/μM, when applied in simultaneous detection of AA, DA, and UA. Whereas, the determination of HQ, CC and RC acquired sensitivity of 0.04, 0.78, and 0.15 μA/μM and LODs of 15, 8, and 39 nM, respectively. The obtained LODs for AA, DA, and UA at AuNPs/ERGO-poly(PR)/GCE were 54, 5.6, and 5.8 nM, respectively. Sensitivity of this electrode in AA, DA, and UA mixture solution was 0.63 μA/μM for UA, 0.40 μA/μM for DA, and 0.48 μA/μM for AA. The three isomers; HQ, CC, and RC showed sensitivies of 4.61, 4.38, and 0.56 μA/μM supplemented by LODs of 53, 53, and 79 nM at the same electrode in their ternary. Both AuNPs/ERGO-pEBT/GCE and AuNPs/ERGO-poly(PR)/GCE showed prominent selectivity toward the analytes (AA, DA, UA and HQ, CC, RC). In addition, no interference effect with possible co-existence ions and compounds that could hinder the analyte detection as well as presenting good repeatability, reproducibility and favourable stability. The as-proposed electrochemical sensors were applied successfully with outstanding recoveries in urine samples, vitamin C tablets and synthetic wastewaters analysis. The modified electrode AuNPs/ERGO-pEBT/GCE offered enhanced efficiency in the simultaneous determination of dihydroybenzene isomers, while the electrode AuNPs/ERGO-poly(PR)/GCE is demonstrated superior performance towards determination of UA,DA, and AA.